Procesos de privatización y desarticulación de tierras indígenas en el norte de Argentina en el siglo XIX - Teruel, Ana A.; Fandos, Cecilia (Revista Complutense de Historia de América, 2010)
The expansion of private property upon the colonial structures that still persisted regarding land issues was one of the priorities in the political agenda of the new National States of Latin America during the second half of the XIXth century. One of the main processes of this subject was the disentailment and privatization of the native properties. This article reviews such process in the provinces of Jujuy, Salta and Tucumán in the North of Argentina, taking into account the impact of the legislative reforms and attempting an approach on the property as a social problem rather than as a simple legal one.